Farms and Fields in the Chilterns - Coppock, John Terence (ERDKUNDE, 1960)
A survey carried out by the Ministry of Agriculture in 1941 gave for the first time a list of the boundaries and sizes of all farms in England and Wales. The present work examines farms and their fields in the Chilterns, a chalk range covered with clay with flints, and in their northern and southern foreland, which consists of valleys with clayey soils (Fig. 1). Whereas in the Chilterns themselves field cultivation and grazing occur side by side, the northern valley is more pastoral; however, between the two areas there is a narrow but distinct belt, the Icknield Belt, which is used only for arable farming (Fig. 2). Farms of medium size (between 40 and 120 ha) occupy the greater part of the total area (Inventory I). Since farms of different sizes are found everywhere, it is only possible to speak about the predominance of a certain size class in certain sub-areas (Fig. 3). Large farms are often found in the main field cultivation areas, while small farms are found only in the parts of the valleys where small tenant farms belonging to the county occur, or in the districts where field vegetable cultivation prevails. The location of the farmsteads is mainly agrarian. In the Chilterns themselves and south of them, enclosure was early - if these were ever Gewannflur areas at all. In the northern valley, about half the land was enclosed by Acts of Parliament between 1750 and 1850 (fig. 4). In the districts of early enclosure, scattered settlement prevails, with farmsteads in the center of their own land; so-called lodge farms. In the districts of later enclosure, the farmsteads, especially of the smaller farms, are often located as Village Farms in the villages. *) This paper is based upon material collected with the help of a grant from the Central Research Fund, University of London. Figures 3, 4, 5, 8 and 9 are derived from the Farm Boundary Maps of the Ministry of Agriculture; they are Crown Copyright and are published with the sanction of the Controller of H. M. Stationery Office. The maps have been drawn by J. BRYANT, R. VERSEY and K. WASS. The land of English farms generally shows very irregular ground plan shapes and everywhere different types are found side by side. Whereas elsewhere in the step land farms with elongated rectangular corridor extending from the valley over the step to the plateau are common, these are absent on the Chiltern step. However, such forms are often found here in the slightly hilly foreland, although there is no physical-geographical reason to use this plan form here (Fig.5). The occurrence of this landform is historical, as it usually coincides with village farms. Most farms in this area are ring-fence farms, meaning they consist of a single piece of land surrounded by an unbroken property line. However, numerous farms also have outside pieces of land or groups of such. Some of these can be explained in their existence by proximity to town or the desire to own a forest parcel. However, most of these outside fields are located in the clayey valleys, which are used almost exclusively for field crops. The mixed situation also resulted in part from the concentration of farms in the villages, the way land was allocated during enclosure, and the piecemeal acquisition or sale of individual land parcels in areas of small farms. In each of the subareas, individual pieces of land occur in a respectable number of different sizes. In the Chilterns themselves, their size varies particularly widely, but pieces over 6 ha make up the bulk. In the Icknield Belt, very large fields are found, some over 100 ha in size. In the foreland, the pieces vary less in size; in the northern valley they are mostly about 4 ha, while in the area of clayey soils in the south of less than 4 ha are very common (Inventory II). The distribution pattern of land pieces of different sizes is similar to that of farms, and there is a relationship both between the sizes of land pieces and farms and between these two and the farming method. Field farming generally shows a tendency toward large farms and fields, and pasture farming toward farms and land pieces of medium size. The land parcels also vary in plan shape (Fig. 6). In the chilterns they are mostly irregular, in the foothills they are often rectangular. The former are found in districts of early enclosure, the latter in districts where enclosure was accomplished by parliamentary decree. In order to study how these different features have changed during the last hundred years, a series of detailed individual studies were carried out. They revealed that the changes that have taken place are extremely complicated in detail; farms in three adjoining townships in the part belonging to Bedford County showed both increases and decreases in size or no change (Fig. 9). In general, however, a tendency for farms to increase in size during this period can be shown. It is similar for land parcels, although subdivisions also occurred. Most of the land parcels, however, remained unchanged (Fig. 10). The changes that occurred were generally distributed throughout the area, so that there was little change in the differences between subdivisions (Fig. 11). A landscape analysis of the agricultural landscape as it was a hundred years ago would therefore show that the distribution pattern of farms and fields differed little from that of today.